DUALISME HUKUM PENETAPAN ADOPSI ANAK - Indriani, Dewi (Gapenas Publisher, 2024)
This article aims to examine the existence of legal dualism in the determination of child adoption in judicial institutions, namely in the Religious Court and the State Judiciary. Dualism in the determination of child adoption in judicial institutions, this is important to study because it will cause uncertainty to the community in determining the choice for the determination of child adoption, especially for Muslims, whether to take the legal route to the Religious Court or to the District Court. This will make the public confused in determining the choice for legal certainty of child adoption in the judicial environment. The community will be uncertain about the legal certainty that they will take. The public will compare the law between the Religious Court and the District Court which will lead them to an assumption or assumption that the Religious Court has stronger legal force than the District Court or vice versa the District Court has stronger legal force compared to the Religious Court